1992
DOI: 10.1128/iai.60.7.2900-2905.1992
|View full text |Cite
|
Sign up to set email alerts
|

Rational attenuation of Corynebacterium pseudotuberculosis: potential cheesy gland vaccine and live delivery vehicle

Abstract: The phospholipase D (PLD) gene (pld) has been deleted from the Corynebacterium pseudotuberculosis chromosome by using site-specific mutagenesis. Sheep infection trials indicate that the PLD-negative C. pseudotuberculosis strain (Toxminus) is incapable of inducing caseous lymphadentis (cheesy gland) even at doses two logs higher than that at which the wild-type strain produces the disease. This clearly establishes PLD as a major C. pseudotuberculosis virulence factor. Vaccination of sheep with live Toxminus C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 22 publications
2
50
0
9
Order By: Relevance
“…PLD assists the spread of Corynaebacteria from the site of infection by causing hydrolysis of vascular and lymphatic endothelial walls. Moreover, PLD contributes to the in vivo survival of C. pseudotuberculosis in the host for at least 18 weeks, thus leading to strong stimulation of the immune system (Hodgson et al, 1992). The production of PLD of C. pseudotuberculosis in tissues of infected animals has been shown to impair neutrophil chemotaxis toward the site of infection thus allowing the escape from neutrophils in addition to its killing ability of the phagocytic neutrophil.…”
Section: Selimmentioning
confidence: 99%
See 1 more Smart Citation
“…PLD assists the spread of Corynaebacteria from the site of infection by causing hydrolysis of vascular and lymphatic endothelial walls. Moreover, PLD contributes to the in vivo survival of C. pseudotuberculosis in the host for at least 18 weeks, thus leading to strong stimulation of the immune system (Hodgson et al, 1992). The production of PLD of C. pseudotuberculosis in tissues of infected animals has been shown to impair neutrophil chemotaxis toward the site of infection thus allowing the escape from neutrophils in addition to its killing ability of the phagocytic neutrophil.…”
Section: Selimmentioning
confidence: 99%
“…This may have lead several authors to attempt the development of living attenuated corynebacterial vaccines against CLA in sheep. With the help of genetic engineering methods, Hodgson et al (1992) could delete the gene responsible for PLD production from the wild strain of C. pseudotuberculosis, obtaining a new non-PLD-producing strain called`Toxminus strain' of Corynebacteria.…”
Section: Immunological Aspectsmentioning
confidence: 99%
“…11 The PLDs from C. pseudotuberculosis, C. ulcerans and A. haemolyticum have been shown to have similar biological effects to Loxosceles venom 11,12,14,15 with C. pseudotuberculosis PLD playing a vital role in the pathogenesis of caseous lymphadenitis in sheep and goats. 16,17 We have previously shown that the lysis of erythrocytes induced by Loxosceles sphingomyelinases is dependent on activation of complement (C) via the alternative pathway, 9,10 which was caused by induction of cleavage of cellsurface glycophorins. 18 The sialic acid on glycophorins increases the binding of factor H (f H; the co-factor for factor I in the degradation of C3b) to surface-bound C3b, 19,20 which can limit activation of the alternative pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that phospholipase D (PLD) of C. pseudotuberculosis was identified as the major virulence factor of 31 KDa and it was suggested that PLD exotoxin facilitate the dissemination and infiltration of the bacteria in host tissues (Hodgson et al, 1992). The duration of lethality depends upon the number of exotoxins contained in the same isolate.…”
Section: Mediamentioning
confidence: 99%